2022
DOI: 10.1155/2022/2323836
|View full text |Cite
|
Sign up to set email alerts
|

Petrochemical Wastewater Treatment by Eggshell Modified Biochar as Adsorbent: Atechno-Economic and Sustainable Approach

Abstract: Petrochemical industrial wastewater (PIW)contains toluene and xylene (TX), and various organic and inorganic pollutants, causing severe risks to human health if improperly released into the environmental matrices. For the long-term reliability of environmental conservation, this study illustrates the interlinkage between PIW treatment and the three pillars of sustainable development. Sewage sludge biochar was modified with eggshell, showing a relatively high fixed C content (increase in carbonization degree), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Both MTBs presented similar adsorption patterns and efficacies. Rapid Cr(VI) adsorption can imply the combination of physical and chemical adsorptions on the adsorption progress, especially for physical adsorption during rapid adsorption progress [19, 37] and the accessibility of large amounts of vacant active sites [39]. Additionally, the inability of adsorbents to remove Cr(VI) at the later stages can indicate the limitation of active sites and slow diffusion of Cr(VI) ions to the interior of the bentonite surface which became full as time progressed [8, 31].…”
Section: Resultsmentioning
confidence: 99%
“…Both MTBs presented similar adsorption patterns and efficacies. Rapid Cr(VI) adsorption can imply the combination of physical and chemical adsorptions on the adsorption progress, especially for physical adsorption during rapid adsorption progress [19, 37] and the accessibility of large amounts of vacant active sites [39]. Additionally, the inability of adsorbents to remove Cr(VI) at the later stages can indicate the limitation of active sites and slow diffusion of Cr(VI) ions to the interior of the bentonite surface which became full as time progressed [8, 31].…”
Section: Resultsmentioning
confidence: 99%
“…Kumi et al [13] represented the application of the pyrolysis process to convert sewage sludge into biochar. The biochar elemental composition was modified by adding eggshell waste, generating an adsorbent suitable for toluene and xylene (TX) removals.…”
Section: Summaries Of Accepted Articlesmentioning
confidence: 99%
“…It has been suggested that the neutral-to-alkaline condition encourages the physical adsorption of oil particles onto coagulants via a sweep flocculation mechanism [7]. An adsorbent material having sufficient amounts of negative charge on its surface would form a strong electrostatic attraction to positively-charged contaminants, depending on solution pH and ionic strength [32]. Chemical modifications could be performed for the cationization of adsorbents, after which they become able to form a strong electrostatic attraction with anionic contaminants.…”
Section: Adsorptionmentioning
confidence: 99%